BPAF-Induced Adipogenesis in 3T3-L1 Cells: Role of Peripheral Serotonin Signaling - Wiggers, Kristina (My University, 2017)
There is evidence that synthetic chemicals in our environment called, obesogens, may play an important role in the global obesity epidemic. Bisphenol A (BPA) is one of the most studied obesogens. Due to concerns surrounding the use of BPA, BPA structural analogues are being used as substitutes in consumer products. However, there is currently little information available regarding their effects on pathways important for the development of obesity. Interestingly, serotonin (5-HT) signaling in peripheral tissues plays an important role in regulating metabolic homeostasis. Moreover, BPA has been shown to alter 5-HT signaling in the central nervous system. Therefore, the objective of this study was to determine the effects of BPA analogues on adipogenesis and elucidate whether their obesogenic effects involve peripheral 5-HT signaling. 3T3-L1 preadipocytes were treated with 10 μM BPA or four commonly used BPA analogues during differentiation. Lipid accumulation was assessed by Oil Red O staining. Adipogenic markers and genes important for 5-HT synthesis/metabolism were subsequently examined following treatment with BPA and the structural analogue bisphenol AF (BPAF). The roles of tryptophan hydroxylase 1 (TPH1) and monoamine oxidase (MAO), in addition to glucocorticoid receptor (GR) signaling were also evaluated. Treatment with 10 μM BPAF and Bisphenol S (BPS) significantly increased lipid accumulation in differentiated 3T3-L1 cells. 10 μM BPAF significantly increased adipogenic gene markers, as well as GR gene transcripts. Moreover, BPAF induced adipogenesis in the absence of the synthetic glucocorticoid dexamethasone. Further, although BPAF significantly increased Tph1 mRNA levels, blocking its activity with para- chlorophenylalanine (pCPA), did not block the adipogenic effects of BPAF. However, co- treatment with the MAO inhibitor, phenelzine, significantly decreased lipid accumulation and peroxisome proliferator activated receptor gamma (Pparg) expression. Therefore, these data demonstrate that BPAF may act as an obesogen and suggests that its action might be mediated, in part, by altered 5-HT signaling.